(untitled) (Bangladesh Journal of Medical Science, 2021)
Introduction: Patient is a 14 years old Chinese boy presented with skeletal Class II with incompetent lips, severe dental Class II malocclusion and severe crowding complicated with both sides mesio-angular impacted of mandibular 2nd molars. Treatment Plan: Growth modification using functional appliance for skeletal Class II correction with maxillary arch expansion and correction of mandibular plane angle by intrusion of maxillary molars. Extraction of lower 1st premolars and 2nd molars on both sides was carried out in conjunction with fixed orthodontic alignment and to facilitate of spontaneous eruption of lower third molar. Midline correction was followed by space closure and finishing and detailing. Results: Alignment of upper arch in the regained space with maxillary expansion without any extraction was done. Anterior maxillary dentitions were retracted using Temporary Skeletal Anchorage Devices (TSADs). In lower arch 1st molars were mesially protracted by using class II elastics. 3rd molars spontaneously erupted in the extraction space of 2nd molar. Midline corrected with good facial profile and competent lips. Conclusions: Timely execution of expert treatment plan can bring cost effective and time saving results with minimum loss. By proper counseling, patient compliance and confidence can be boosted which could have a positive effect on the treatment outcome. Bangladesh Journal of Medical Science Vol.20(3) 2021 p.682-690